1989
DOI: 10.1007/bf02330707
|View full text |Cite
|
Sign up to set email alerts
|

β-Endorphin/β-lipotropin release and gonadotropin secretion after acute exercise in physically conditioned males

Abstract: beta-endorphin (beta-EP) and beta-lipotropin (beta-LPH) concentrations were measured in the basal state and after acute exercise for 15 min or until exhaustion in 6 physically conditioned male volunteers. Serum concentrations of luteinizing hormone (LH), follicle stimulating hormone (FSH), testosterone and prolactin were also measured in the basal state. In addition, the concentrations of the gonadotropins (LH and FSH) were determined after exercise and the gonadotropin response to gonadotropin releasing hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Such increases in b-endorphin concentration were observed early in exercise (i.e., 5±10 min.). Some investigators who also employed vigorous but less intense protocols (i.e., 80±85% of maximal HR) failed to show any signi®cant changes in b-endorphin concentration during exercise (Bullen et al 1984;Elias et al 1989). Moreover, other investigators have also reported no signi®cant changes in b-endorphin concentration during exercise of low to moderate intensity (Goldfarb et al 1991;McMurray et al 1987).…”
Section: Discussionmentioning
confidence: 98%
“…Such increases in b-endorphin concentration were observed early in exercise (i.e., 5±10 min.). Some investigators who also employed vigorous but less intense protocols (i.e., 80±85% of maximal HR) failed to show any signi®cant changes in b-endorphin concentration during exercise (Bullen et al 1984;Elias et al 1989). Moreover, other investigators have also reported no signi®cant changes in b-endorphin concentration during exercise of low to moderate intensity (Goldfarb et al 1991;McMurray et al 1987).…”
Section: Discussionmentioning
confidence: 98%
“…However, infertility is uncommon in male athletes (9). Attenuated LH response to GnRH stimulation has been shown in long-distance runners (11), but the gonadotropin response to GnRH stimulation is reported to be uninfluenced by acute short-term exercise to exhaustion (14). Also, the overtraining syndrome has been related to hypothalamic dysfunction: ACTH, GH and prolactin responses to insulin-induced hypoglycemia was attenuated in overtrained athletes (15).…”
mentioning
confidence: 99%
“…Alterations in circulating ~-endorphin levels have been considered responsible for short-term and chronic exercise-associated suppression of the HPG axis in both men and women. This has been difficult to prove, since opiate antagonism does not prevent the exercise-induced decrease in LH observed by some, but by no means all investigators (14,49,52,53,57,58). Gonadotropin response to GnRH has been reported as reduced and increased following prolonged, exhaustive exercise (53,59).…”
Section: The Effects Of Prolonged Exercise On the Hpg Axis In Menmentioning
confidence: 99%
“…GnRH-induced LH response appears to be impaired (58). No evidence has supported increased opioidergic tone as being important in the generation of GnRH-LH suppression in athletes, but the effects of catecholamines have received little attention (57,102). Chronic elevation of serum cortisol levels has been associated with overtraining, but cortisol levels are usually nonnal in male endurance-trained runners (104).…”
Section: Mechanisms Of Exercise-associated Reductions In Serum Testosmentioning
confidence: 99%